Breast conserving surgery with immediate partial breast reconstruction using a latissimus dorsi mini flap: oncological clearance and cosmetic outcomes - A., Raflis Ruzairee; T., Ju Ann; A. A., Nur Aziah; D., Nor A. Hakim; E., Nur Aina (International Surgery Journal, 2022)
Background: In our center, a breast conserving surgery (BCS) with immediate partial breast reconstruction using a latissimus dorsi mini flap (LDMF) is performed in women with a large tumor-to-breast-size ratio who declined mastectomy. We conducted a study to assess the oncological clearance and cosmetic outcomes following a BCS with immediate LDMF partial breast reconstruction in women with various breast pathologies. Methods: A cross-sectional study was conducted involving patients who underwent a BCS with immediate LDMF reconstruction between January 2016 and January 2021 in the hospital Kuala Lumpur, Malaysia. The demographic data, tumor characteristics, operative details and post-operative complications were documented. The histopathological reports were reviewed to determine the oncological clearance. Patient’s satisfaction on the cosmetic outcomes evaluated using a standard breast-Q questionnaire. Results: Thirty patients with various breast pathologies were recruited; invasive carcinoma (n=26, 86.7%), ductal carcinoma in-situ (DCIS) (n=1, 3.3%), phyllodes tumor (n=2, 6.7%), and dermatofibrosarcoma protuberans (n=1, 3.3%). The mean tumor size was 4.92 cm, giving the mean specimen weight of 224 g. Adequate oncological clearance was obtained in 96.7% of all cases. Seventeen of the patients (n=17, 56.6 %) were deeply satisfied and the remaining patients were satisfied (n=13, 43.3 %). Conclusions: In a stage II/III breast cancer, a BCS with immediate partial breast reconstruction using a LDMF can be safely performed with satisfactory cosmetic outcomes in women with a large tumor-to-breast-size ratio.